Pengaruh Pembiayaan Murabahah,Musyarakah dan Mudharabah Terhadap Profitabilitas Bank Umum Syariah di Indonesia (Studi Empiris Pada Bank Umum Syariah di Indonesia Tahun 2011-2014) - Fadholi, Amri Dziki; , Drs. Atwal Arifin. Akt, M.Si (2015)
This research aims to analyse the influence of murabahah,musyarakah and mudharabah on the level of profitability in Indonesian syariah banking by using the ratio of Return On Assets (ROA). The method used is descriptive quantitative approach of research and case studies on Indonesia Syariah Banks.Types of data obtained from this research is secondary data based on quarterly financial reports from the result of Indonesia Syariah Banking,There are BNI Syariah,Bank Syariah Mandiri,BRI Syariah,Bank Muamalat and Panin Bank Syariah during from 2011 annual reports until 2014.Data sources obtained through publication results by on the Bank Indonesia's website or www.bi.go.id.Analysis tools are used multiple linear regression analysis. The research results show that the financing murabahah and musyarakah to exert an influence on the level of significant ROA,while financing mudharabah give a positive influence on the level of ROA and significant partial evaluation.Simultaneously,murabahah, musyarakah and mudharabah provides significant influence on the level of ROA.Mudharabah is dominant for make influence on the level of Return on Assets. Keywords : Murabahah,Musyarakah,Mudharabah financing,Profitability, Return On Assets,Indonesia Syariah Banks